The Impact of Project Strategies’ Implementations on Eighth Grade Students’ Proficiency in Crafting Argumentative Paragraphs - Arli Mastani; Afore Tahir Harefa (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This experimental study investigates the impact of Project Strategy on the argumentative writing skills of eighth-grade students. The study aims to (1) evaluate the students' writing proficiency using Project Strategy, (2) assess their skills without this strategy, and (3) determine if Project Strategy significantly enhances their writing ability. The population consists of 120 students, with a sample of 60 students selected randomly. Data were collected through essay tests, and a pretest confirmed the groups' homogeneity. The experimental group's mean pretest score was 63.00, while the control group's was 53.50. Post-treatment, the experimental group's mean score improved to 73.33, indicating a good proficiency level, compared to the control group's 63.67, which was deemed adequate. Hypothesis testing showed a significant effect (tcount = 5.110, ttable = 2.002), suggesting that Project Strategy positively influences students' writing abilities. Based on these findings, it is recommended that English teachers adopt innovative strategies to improve writing skills, emphasizing the importance of effective paragraph construction in English education.